Inverted takotsubo syndrome complicated with cardiogenic shock requiring veno-arterial extracorporeal membrane oxygenation in a patient with bilateral pheochromocytoma: a case report. Issue 2 (16th March 2020) - Faria, Bebiana Manuela Monteiro; Português, João; Roncon-Albuquerque Jr, Roberto; Pimentel, Rodrigo
Abstract: Background: Takotsubo syndrome (TS) is characterized by a transient left ventricular (LV) dysfunction and rarely presents with cardiogenic shock (CS). Inverted TS (ITS) is a rare entity associated with the presence of a pheochromocytoma. Case summary: We present a case of a young woman was admitted to the emergency department due to intense headache, chest discomfort, palpitations, and breathlessness. An ITS secondary to a pheochromocytoma crisis presenting with CS was diagnosed. The patient was managed with veno-arterial extracorporeal membrane oxygenation, until recovery of LV function. On the 35th day of hospitalization, open bilateral adrenalectomy was performed. Discussion: Takotsubo syndrome patients presenting with CS are challenging and clinicians should be aware of underlying causes. Specific triggers such as pheochromocytoma should systematically be considered particularly if ITS was presented. Extracorporeal life support devices could provide temporary mechanical circulatory support in patients with TS on refractory CS and help to manage complex cases with TS due to pheochromocytoma.